Enhanced Fumagillin Production by Optimizing Fermentation and Purification Techniques - Zili Feng; Pengfei Du; Yunzhi Sheng; Bin Wang; Wang Chen; Hao Peng (Fermentation)
Fumagillin is a complex biomolecule. Nowadays, the separation and purification techniques of fumagillin still need to be optimized. In this study, the yield of fumagillin was examined in relation to temperature, pH, inoculation volume, rotation speed, and liquid volume. By using single-factor optimization, a factorial design, and response surface methodology, the fumagillin yield increased from 10~15% to 30~35%. After scaling up the fermentation process, the fumagillin yield remained stable at 30–35%. In addition, fumagillin was prepared via high-performance preparative liquid chromatography; the yield of the preparation was 77.29%, and the purity was greater than 99%. To sum up, these findings demonstrated that the issue of low fumagillin yield can be resolved by optimizing the fermentation process and introducing the high-performance liquid chromatographic method for the rapid preparation of fumagillin with high recoveries. The findings of this study may serve as a foundation for the large-scale production of fumagillin.